2009
DOI: 10.1093/gerona/glp146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Overload on Muscle Hypertrophy and mTOR Signaling in Young Adult and Aged Rats

Abstract: 24% higher in Y SA and O SA compared with CON ( p = .009). Eukaryotic initiation factor 2B e phosphorylation was 33% and 9% higher in Y SA and O SA compared with CON ( p = .04). Translational signaling in young adult and aged plantaris muscle is equally responsive to chronic overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…This result is similar to the lack of differences in translational signaling with overload hypertrophy despite an attenuated growth response (Chale-Rush et al, 2009). We hypothesized that muscles from aged rats would show a blunted recovery of muscle size with regrowth in pathways responsible for the balance between protein synthesis and degradation, but failed to prove this hypothesis for most pathways at the time point measured, even though there were some differences in aged muscle in general which may have influenced the regrowth response.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This result is similar to the lack of differences in translational signaling with overload hypertrophy despite an attenuated growth response (Chale-Rush et al, 2009). We hypothesized that muscles from aged rats would show a blunted recovery of muscle size with regrowth in pathways responsible for the balance between protein synthesis and degradation, but failed to prove this hypothesis for most pathways at the time point measured, even though there were some differences in aged muscle in general which may have influenced the regrowth response.…”
Section: Discussionsupporting
confidence: 77%
“…Muscle size lost due to starvation, glucocorticoid treatment, hind limb suspension, and limb immobilization was not recovered to the same extent in old as in young rats (Dardevet et al, 1995; Hao et al, 2011; Magne et al, 2011; Mosoni et al, 1999; Zarzhevsky et al, 2001a; Zarzhevsky et al, 2001b) and the growth response to intermittent mobility during atrophy is also inhibited (Gallegly et al, 2004). Similarly, muscle hypertrophy in response to overload is impaired in aged animals (Chale-Rush et al, 2009; Degens and Alway, 2003; Thomson and Gordon, 2006) indicating that aged muscle responds differently to a similar growth stimulus than young muscle. However, previous studies have shown contradictory results when investigating cellular mechanisms potentially responsible for the impaired growth response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that the higher mTOR and S6K1 phosphorylation was associated with increased mTORC2 signaling and insulin resistance in older adults [64]. We also propose that mTOR hyperphosphorylation may contribute to anabolic resistance of aging, which is the reduced ability of aged muscle to phosphorylate mTOR and activate protein synthesis in response to anabolic stimuli such as exercise 25, 46, [65], [66], insulin 33, 38 and nutrition 67, 68 . A recent paper reported a lower mTORC1 signaling in older men as compared to younger men [67].…”
Section: Discussionmentioning
confidence: 99%
“…p70S6K activation, which is critical for protein synthesis, has been reported to the same [83] or increased [85] in old rats compared to adults. Using a synergist ablation model of muscle growth whereby the gastrocnemius muscle is partially ablated to cause growth in the synergist plantaris muscle, old rats had similar patterns of activation of the Akt/mTOR pathway as young rats, although the magnitude of increase in plantaris muscle mass was less for old rats than for young rats [86]. While there are conflicting results regarding changes in the Akt/mTOR pathway in studies using animal models of aging, most animal models of sarcopenia report an aging-related decline in muscle mass [80, 82, 84-86], suggesting that even if there is an increase in protein synthesis that occurs with aging it is not enough to keep up with other changes in the muscle that contribute to sarcopenia.…”
Section: Aging-related Changes In Signaling Pathways That Regulate Skmentioning
confidence: 99%